THE ROLE OF CHARACTERS OF A TRADITIONAL SOCIETY IN COMMUNITY DEVELOPMENT BASED ON LOCAL KNOWLEDGE (Interpretative Study on the Community of Ternate City) - Natalia Rahman Damayanti (ISTORIA: Jurnal Pendidikan dan Sejarah, 2020)
This research entitled The Role of Indigenous Peoples in Community Development Based on Local knowledge, with a qualitative research method with a phenomenological interpretive research approach. This research was conducted with ten subjects, eight of whom were traditional community leaders of the Sultanate of Ternate and two others were heads of departments at the Ternate City Cultural Office. The problem in this study is that modernization can eliminate local knowledge in Ternate, so the role of traditional community leaders is very much needed. The purpose of this study is to describe the role of traditional community leaders in the development of Ternate City. After the research was carried out, the roles were described in simple terms: (1) Betuk roles, including adat seatorang, sere se duniru, bobaso se rasai, cing se cingare, galib se lakudi. (2) Expectations for roles, namely expectations of something said, done, and shown by traditional community leaders. (3) The image in the role, namely everything that is said, done, and also shown by traditional community leaders is used as an example by the Ternate community. (4) The quality of the role, namely the quality produced by a role played by traditional community leaders. Then the results of this study were analyzed using ethnodevelopment development theory from Bjorn Hettne and local knowledge from Clifford Geertz. One thing that can be learned from ethnodevelopment is that it is impossible to apply the formula for community development, without considering the unique historical, social, legal, and economic relationships of each culture, and what can be underlined from local Knowledge according to Clifford Geertz is a value that is considered good and also true so that it can last a long time, even institutionalized. In conclusion, traditional community leaders live accompanied by the values of local knowledge that are applied in daily life, the importance of knowledge of history, customs and culture makes the application of local knowledge values unstructured but always exists. Keywords: Role, Indigenous Community Figures, Local knowledge